Microbial Carbonic Anhydrases in Biomimetic Carbon Sequestration for Mitigating Global Warming: Prospects and Perspectives - Bose, Himadri; Satyanarayana, Tulasi (Frontiers in Microbiology, 2017)
Global warming is causing havoc on the climate, thus, many leading cities in the world are becoming tough for living. Biomineralization of carbon dioxide using carbonic anhydrase (CA) is one of the most economical methods for mitigating global warming. The temperature of flue gas is quite high and alkaline conditions favour precipitation of CaCO3 in the mineralization process, therefore, thermo-alkali-stable CAs are essentially required for biomimetic carbon sequestration. CAs must be stable in the presence of various flue gas contaminants too. The extreme environments on earth harbor a variety of polyextremophilic microbes that are rich sources of thermo-alkali-stable CAs. CAs are the fastest among the known enzymes, which are of six basic types with no apparent sequence homology, thus represent an elegant example of convergent evolution. The current review focuses on the utility of thermo-alkali-stable CAs in biomineralization based strategies. A variety of roles that CAs play in various living organisms, the use of CA inhibitors as drug targets and strategies for over production of CAs to meet the demand are also briefly discussed.